Effect of Yeast (Xanthophyllomyces Dendrorhous) and Plant (Saint John S Wort, Lemon Balm, and Rosemary) Extract Based Functional Diets on Antioxidant and Immune Status of Atlantic Salmon (Salmo Salar) Subjected to Crowding Stress - Spencer-Ossa, E; Sandino-Garcia, A; Imarai-Bahamonde, C; Vargas-Valenzuela, D (Academic Press, 2018)
Salmon farming may face stress due to the intensive culture conditions with negative impacts on overall performance. In this aspect, functional feed improves not only the basic nutritional requirements but also the health status and fish growth. However, to date no studies have been carried out to evaluate the effect of functional diets in salmon subjected to crowding stress. Thus, the aim of this study was to evaluate the effect of yeast extract (Xanthophyllomyces dendrorhous; diet A) and the combination of plant extracts (common Saint John s wort, lemon balm, and rosemary; diet B) on the antioxidant and immune status of Atlantic salmon grown under normal cultured conditions and then subjected to crowding stress. Fish were fed with functional diets during 30 days (12 kg/m3) and then subjected to crowding stress (20 kg/m3) for 10 days. The lipid peroxidation in gut showed that both diets induced a marked decrease on oxidative damage when fish were subjected to crowding stress. The protein carbonylation in muscle displayed at day 30 a marked decrease in both functional diets that was more marked on the stress condition. The expression of immune markers (IFNγ, CD4, IL-10, TGF-β, IgMmb, IgMsec, T-Bet, and GATA-3) indicated the upregulation of those associated to humoral-like response (CD4, IL-10, GATA-3) when fish were subjected to crowding stress. These results were confirmed with the expression of secreted IgM. Altogether, these functional diets improved the antioxidant status and increased the expression of genes related to Th2-like response suggesting a protective role on fish subjected to crowding stress. © 2017